Rural Jail Reentry and Mental Health: Identifying Challenges for Offenders and Professionals. (January 2016) - Ward, Kyle C.; Merlo, Alida V.
The current study examines the challenges of rural jail reentry including mental health issues faced by offenders returning from jails. This study compared a sample of 200 current jail inmates, 166 probation/parole officers working in rural areas, and 21 rural treatment staff working with former offenders in a treatment capacity. Overall, inmates found structural issues (e.g., employment, housing, ability to pay fines) to be more challenging while practitioners were more likely to rank personal issues (e.g., lack of motivation, temptation to reoffend) as more problematic. Various themes emerged relating to mental health issues including health insurance, medication, transportation, and co-occurrence with substance abuse. Policy implications and recommendations for the future are discussed.